2020
DOI: 10.15835/buasvmcn-hort:2020.0016
|View full text |Cite
|
Sign up to set email alerts
|

Yield Performance of Faba Bean Cultivars under Different Environmental Conditions in Greece

Abstract: Faba bean is an important grain legume, grown for human consumption and animal feed and can be used as an alternative to soybean protein. Drought and heat strongly influence faba bean growth and production, especially in flowering and pod development stages. The aim of this study was to determine the response of six cultivars to different environmental conditions during the 2018-2019 growing season. Four inbred lines and two commercial cultivars were sown in different environments in South, Central and North G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…It appears to be generally true that there are no appreciable variations between three irrigations of slightly different magnitudes that are applied and regular irrigation (control). Similar results were also obtained by [17][18][19][20][21][22].…”
Section: One =One Irrigation At Beginning Of Flowering (Bf) Two =Two ...supporting
confidence: 90%
“…It appears to be generally true that there are no appreciable variations between three irrigations of slightly different magnitudes that are applied and regular irrigation (control). Similar results were also obtained by [17][18][19][20][21][22].…”
Section: One =One Irrigation At Beginning Of Flowering (Bf) Two =Two ...supporting
confidence: 90%
“…These results are in the line with those accomplished by . [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26] Data in table (2) exert that faba bean densities evidentiate there were significantly differences in seeds weight kg plot-1 in both seasons. The results indicates that density 20 kg/fed was the highest seeds weight ( 0.143 kg plot-1), followed by density 30 kg/fed ( 0.131 kg plot-1) then density 40 kg/fed (0.123 kg plot-1) in the first and in the second seasons density 30 kg/fed was the highest seeds weight ( 1.035 kg plot-1), followed by density 20 kg/fed ( 1.029 kg plot-1) then density 40 kg/fed (1.018 kg plot-1), respectively .…”
Section: Results and Discussion -Impact Of Varying Densities Of Faba ...mentioning
confidence: 99%
“…A positive correlation between maturity and yield was found in the control condition, but not in the stress treatment. Katsoulieri et al. (2020) described that later ripening genotypes showed greater susceptibility to drought stress during early pod set compared to genotypes with early maturity.…”
Section: Discussionmentioning
confidence: 99%
“…A positive correlation between maturity and yield was found in the control condition, but not in the stress treatment. Katsoulieri et al (2020) described that later ripening genotypes showed greater susceptibility to drought stress during early pod set compared to genotypes with early maturity. This was supported by Khan et al (2010) as well as Manning et al (2020), where early flowering is considered an important adaptation trait for cool-season legumes growing under semi-arid conditions.…”
Section: Correlations Cluster Analysis and Principal Component Analysismentioning
confidence: 99%